Sleep patterns and quality in university students: characteristics and associated factors: Sleep quality in university students - de Souza Vasconcelos, Danilo; Vitória Silva dos Santos, Kellen; Cristina Linhares Viana, Débora; Tâmara do Nascimento Diniz, Isabeli; Carlos Oliveira Silva, Ian; Siqueira Torres Borges, Maria Clara; Gabrielle de França Ferreira, Luana (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Sleep is vital and influenced by factors such as age, lifestyle, and mental health. College students are always faced with challenges that negatively compromise their sleep and well-being. Objective: To evaluate sleep quality and associated factors among university students. Methods: This was a cross-sectional and quantitative study with 294 students from a public university in northeastern Brazil. Questionnaires on social and health characteristics, the Pittsburgh Sleep Quality Index, the Munich Chronotype Questionnaire, and the Perceived Stress Scale were used for data collection. Results: The study included 294 students with an average age of 21.5 years, 52.7% female, 43.7% from the health field, and 56% from the daytime shift. There was a prevalence of 76.5% of poor sleep quality, with the most impacted components being sleep latency, daytime dysfunction, sleep disturbances, and subjective sleep quality. The average sleep duration on school days was 416 min ± 88min, with 69.4% using an alarm clock. The students exhibited a slightly evening chronotype, correlating with greater social jetlag (r = 0.510; p < 0.001). Students who engaged in physical exercise had better sleep quality (7.9±3.5 vs 9.2±3.9; p = 0.005) and lower stress levels (22±6.1 vs 24.6±6.7; p < 0.001). Additionally, poor sleep quality was also correlated with higher stress (r = 0.326; p < 0.001) and eveningness (r = 0.244; p <0.01). Conclusion: The study highlights the high prevalence of poor sleep quality among university students, correlated with stress and eveningness. Physical exercise improves sleep quality and reduces stress, demonstrating its importance for student health.